Making the Void Fruitful Yeats as Spiritual Seeker and Petrarchan Lover - Keane, Patrick J. (Open Book Publishers, 2021)
Shedding fresh light on the life and work of William Butler Yeats-widely acclaimed as the major English-language poet of the twentieth century-this new study by leading scholar Patrick J. Keane questions established understandings of the Irish poet's long fascination with the occult: a fixation that repelled literary contemporaries T.S. Eliot and W.H. Auden, but which enhanced Yeats's vision of life and death. Through close reading of selected poems, the first section of Making the Void Fruitful assesses Yeats's spiritualised treatment of corporeal themes, exploring sex and eroticism as the expression of a duality inherent to his ontological and supernatural convictions. The power-producing tension in Yeats's work is not only intellectual but emotional. At its vital centre is his Muse: the beautiful political firebrand, Maud Gonne, whose activist Republican politics he considered his one real rival. Through close engagement with the poems and plays she inspired, the second section explores Yeats's complex relationship with Maud, an obsessive and unrequited love which he sublimated and transformed into the greatest body of Muse poetry since Petrarch, in whose tradition of spiritualized eroticism Yeats, perhaps the last of the great Romantics, was consciously writing. Shaped by the conviction that no modern poet exceeded Yeats in animating the enduring themes of love and spirituality through poetry, this book emphasises the influence, of Blake, Nietzsche, and John Donne, on what Yeats called 'the thinking of the body'. Grounded firmly in the textual materiality of Yeats's oeuvre, this book will be of interest to researchers and students of W.B. Yeats, as well as to those in the fields of Anglophone literatures and cultures, and philosophy.